Festival Istiqlal sebagai Kesadaran Masyarakat dalam Membangun Islam Nusantara - Riza Dewi Al Ardi (Fakultas Dakwah IAIN Jember, 2021)
The chaotic life of Muslims in various parts of the world. This is important when Muslims are in a tough test. the problem of terrorism and radicalism in the name of religion. The challenges of globalization and modernization which are very aggressively spreading the